Modified cellulose membrane with good durability for effective oil-in-water emulsion treatment. (20th February 2019) - Xu, Xi; Long, Yuwei; Li, Qing; Li, Daikun; Mao, Daoyong; Chen, Xinhong; Chen, Yashi
Abstract: Industrial spilled oil and oily wastewater have caused serious environmental pollution and energy dissipation. Hence, a robust cellulose-based filter paper-polyvinyl alcohol (cellulose-PVA) membrane for efficient oil-in-water emulsion separation was fabricated by a universal method of hydroxyl oxidation for any substrate containing hydroxyl groups that was cost-effective and easy to scale up. The resulting membrane exhibited superhydrophilicity, superoleophilicity in air, and stable superoleophobicity under various pH value solutions with contact angles exceeding 150°. The cellulose-PVA membrane can dispose of many types of surfactant-stabilized and different oil droplet sized oil-in-water emulsions with 98.75 % efficiency driven only by gravity without consideration the secondary processing problem. Furthermore, sand paper abrasion tests, tape peeling tests and chemical corrosion resistance tests were executed, indicating the excellent mechanical stability and superior durability of the cellulose-PVA membrane. These results suggest that it is a prospective and competitive candidate for industrial oil-in-water emulsion treatment. Graphical abstract: A cellulose-based filter paper-polyvinyl alcohol membrane was fabricated by a universal method with good durability that is used to effectively separate various oil-in-water emulsions with high oil rejection under gravity. Highlights: The fabrication method is universal for substrates with hydroxyl groups. The membrane can separate different types and droplet sized oil-in-water feeds. More than 99 % oil rejection was achieved driven by gravity. The durability of cellulose-PVA membrane was better.